Evaluation of the Permeation Properties of Concrete Added with a Petrochemical Industry Waste (2015)
In this work, the evaluation of the performance of concrete added with a petrochemical industry waste called Fluid Catalytic Cracking Catalyst residue (FCC) from a Colombian petroleum company is presented. Results of this concrete are compared, with the results of concrete added with a pozzolan with similar characteristics such as the Metakaolin (MK). The analysis of the pozzolanic materials included the determination of the particle size, the pozzolanic activity, and the chemical and mineralogical composition. Different percentages of FCC were used as Portland cement replacement in proportions of 0, 10, 20 and 30 %; similarly concrete added with 20 % of MK as replacement was elaborated. The curing time was 28, 56, 90 and 180 days. These concretes were evaluated through the permeation properties such as: total absorption, porosity, surface absorption and capillary absorption. Results showed that concrete with FCC and MK had similar behavior, and slightly superior than the control sample. The total absorption and porosity were less than 3 % and 10 % respectively for the all of the samples; it means that these concretes had good quality and compactness. The results of surface absorption and capillary absorption showed that these concretes had low permeability too. This behavior is enhanced with the curing age.